2018
DOI: 10.1055/s-0044-101617
|View full text |Cite
|
Sign up to set email alerts
|

Erhöhter Augeninnendruck für 7 Wochen induziert lokale Gefäßveränderungen im experimentellen Glaukommodell in vivo

Abstract: Retinal arterioles and optic nerve capillaries respond sensitively to abnormal pressure elevation in vivo, showing high and early vulnerability. The vascular responses may influence secondary neuronal responses, which culminate in the death of ganglion cells and blindness, as occurs in clinical glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Studies have provided evidence that compared with healthy individuals, the blood flow in the eyes of glaucoma patients is significantly reduced, furthermore, the blood flow in the optic papilla region is reduced more obviously [ 62 , 63 , 64 ]. Furthermore, this was also demonstrated in our previous study in an in vivo glaucoma animal model, elevated IOP leads to shrinking of retinal vascular caliber [ 65 ], which limits the blood flow and oxygen supply in the retina and consequently promotes the production and accumulation of ROS [ 66 ]. Morphological and functional changes of the vascular play a central role in hemodynamic changes.…”
Section: The Anti-oxidative Properties Of H 2 S In Glaucomasupporting
confidence: 61%
“…Studies have provided evidence that compared with healthy individuals, the blood flow in the eyes of glaucoma patients is significantly reduced, furthermore, the blood flow in the optic papilla region is reduced more obviously [ 62 , 63 , 64 ]. Furthermore, this was also demonstrated in our previous study in an in vivo glaucoma animal model, elevated IOP leads to shrinking of retinal vascular caliber [ 65 ], which limits the blood flow and oxygen supply in the retina and consequently promotes the production and accumulation of ROS [ 66 ]. Morphological and functional changes of the vascular play a central role in hemodynamic changes.…”
Section: The Anti-oxidative Properties Of H 2 S In Glaucomasupporting
confidence: 61%
“…The artery enters the eye through the optic nerve and travels through the center of the optic nerve to reach the retina. The CRA then divides into multiple smaller branches that supply blood to the inner retina, which includes the ganglion cells, inner plexiform layer, and inner nuclear layer [17,21]. The choroidal circulation is a network of blood vessels that lies between the retina and the sclera, the outermost layer of the eye.…”
Section: The Anatomy Of Blood Supply In the Retinamentioning
confidence: 99%
“…Retinal vascular dysfunction has been observed as a secondary manifestation both in individuals diagnosed with glaucoma and animal models employed to study the disease, suggesting that glaucoma may also serve as the instigator of retinal vascular abnormalities [16]. These secondary manifestations encompass various alterations, such as a notable reduction in retinal vascular diameter [17], decreased retinal vascular density [18], disturbances in retinal vascular molecules [19], impaired autoregulation of blood flow, dysfunction of retinal arterioles [16], and instances of retinal vein occlusion [17,20]. In this section, we aim to provide a comprehensive and in-depth discussion of the aforementioned alterations observed in both glaucoma patients and animal models used for studying the disease.…”
Section: Glaucoma Can Also Be the Instigator Of Retinal Vascular Abno...mentioning
confidence: 99%
See 1 more Smart Citation
“…MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions, or products referred to in the content. 2 hand, it has been observed that retinal vascular abnormalities are a secondary manifestation of glaucomatous neurodegeneration, suggesting that glaucoma itself may also induce retinal vascular abnormalities [ 8,9]. Studies demonstrate that impaired RGCs require reduced blood supply, causing retinal arteriolar constriction [7].…”
Section: Introductionmentioning
confidence: 99%